Design of contracted and tip loaded propellers by using boundary element methods and optimization algorithms. (February 2016) - Gaggero, Stefano; Gonzalez-Adalid, Juan; Perez Sobrino, Mariano
Highlights: Contracted and tip loaded propellers represent a valid alternative to conventional propulsors. Cavitation and tip vortexes have to be controlled already in the design phase. Traditional design methods may fail with such unconventional geometries and requirements. A feasible alternative is represented by coupled panel code/optimization algorithms. Results on CLT propellers are validated by means of experimental measurements and RANSE calculations. Abstract: In present work, a design by optimization of contracted and tip-loaded (CLT) propellers is proposed and implemented. The design approach is based on a parametric description of the propeller blade, derived from the usual design table by using B-Spline parametric curves, and an in-house developed Panel Method/Boundary Element Method (BEM) aimed to evaluate the performance (including cavitation) of the propellers selected by a genetic optimization algorithm. The modeFRONTIER optimization environment drives the entire design process. A preliminary sensitivity study is carried out to evaluate the effect of the discretization meshes for BEM and RANSE calculations. Based on this analysis, Boundary Element Method and RANSE results over the parent propeller, in terms of both open water propeller performance, unsteady cavitation and induced pressure pulses, are compared with the available experimental measurements in order to validate the adopted design approach. Finally, to assess the reliability of the design by optimization, a set of optimized geometries, selected on the basis of the fulfillment of the design objectives, are checked by means of dedicated RANSE calculations.